(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
The existence of a tribunal system, in addition to helping to smooth the administration system, is considered as sharing power with the judiciary in making decisions. Thus arose the question of decision-making power and prevention of abuse by the administrative body. In line with the sustainable development goals 2030 to ensure justice in support of effective, responsible and inclusive institutions, transparent and fair practices are essential for ensuring people’s trust in the administrative body and government. This paper, therefore, discusses the tribunal system and its implementation in malaysia. In view of this, tribunal systems that exist in other countries, especially the united kingdom, are also examined as models for improvement. Matters such as autonomy or control of power and the trial process are among the issues raised. Recommendations for improvement are proposed based on three basic principles-openness, fairness and impartiality-to further strengthen the implementation of the existing tribunal system in line with developments abroad. Keywords: Tribunal, administrative body, authority, Malaysia, legislature, decision-making